2014
DOI: 10.1017/s0007485314000388
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of geographical separation on the genetic population structure of sympatric species of mites in avocado orchards

Abstract: Oligonychus punicae and Oligonychus perseae (Acari: Tetranychidae) are the most important mite species affecting avocado orchards in Mexico. Here we used nucleotide sequence data from segments of the nuclear ribosomal internal transcribed spacers (ITS1 and ITS2) and mitochondrial cytochrome oxidase subunit I (COI) genes to assess the phylogenetic relationships between both sympatric mite species and, using only ITS sequence data, examine genetic variation and population structure in both species, to test the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Thus, it is uncertain whether or not there is overlap in the potential cryptic species reported in the 2 studies. Previously, Guzmán-Valencia et al (2014) detected similar levels of divergence in COI among morphologically identified O. perseae populations from the states of México and Michoacán, but again these specimens were not recognized by the authors as potential cryptic species, nor can we be certain how they relate to ours. Combined, these key studies provide very strong evidence for the existence of a cryptic species complex in O. perseae, and highlight the importance of considering multiple genetic loci in the assessment of such complexes (i.e., not just COI).…”
Section: Discussionmentioning
confidence: 44%
See 4 more Smart Citations
“…Thus, it is uncertain whether or not there is overlap in the potential cryptic species reported in the 2 studies. Previously, Guzmán-Valencia et al (2014) detected similar levels of divergence in COI among morphologically identified O. perseae populations from the states of México and Michoacán, but again these specimens were not recognized by the authors as potential cryptic species, nor can we be certain how they relate to ours. Combined, these key studies provide very strong evidence for the existence of a cryptic species complex in O. perseae, and highlight the importance of considering multiple genetic loci in the assessment of such complexes (i.e., not just COI).…”
Section: Discussionmentioning
confidence: 44%
“…Unfortunately, no molecular data is currently available for O. peruvianus and we were unable to secure authoritatively identified specimens for inclusion in the current study. Ultimately, the insight from our study and Guzmán-Valencia et al (2014 highlight the need to develop and validate unambiguous species identification methods for pest mites infesting avocados (Skoracka et al 2015). Fig.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations